Health Centers’ Preparedness for Coronavirus (COVID-19) Pandemic in South Wollo Zone, Ethiopia, 2020 - Ayele FY; Zerga AA; Tadese F (Dove Medical Press, 2021)
Fanos Yeshanew Ayele, Aregash Abebayehu Zerga, Fentaw Tadese School of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Aregash Abebayehu Zerga Email aregusina@gmail.comBackground: COVID-19 is a highly contagious respiratory disease caused by severe acute respiratory syndrome coronavirus two (SARS-CoV-2). Preparedness of health facilities to prevent the spread of COVID-19 is an immediate priority to safeguard patients and healthcare workers and to reduce the spread of the pandemic. However, the preparedness of health centers in south Wollo zone is unknown.Objective: To assess the preparedness of Health Centers for COVID-19 in South Wollo Zone, Ethiopia, 2020.Methods: Health facility-based cross-sectional study was conducted among forty-six Health Centers in South Wollo zone in August 2020. The sampled health centers were selected by lottery method. The data was collected from the manager of the health centers using a pretested interviewer-administered and observational checklist. The ReadyScore criteria was used to classify the level of preparedness, in which health centers with a score of > 80%, 40– 80%, and < 40% were considered as better prepared, work to do, and not ready, respectively.Results: In this study, the median score of health centers preparedness for COVID-19 was 70.3 ± 21.6 interquartile ranges with a minimum score of 40.5 and the maximum score of 83.8. Only 12 (26.1%) of the health centers were prepared for the COVID-19 pandemic. The majority (73.9%) of the health centers were found within the group of “work to do”. Conversely, none of the health centers were found within the “not ready” or below group.Conclusion: This study concluded that the preparedness status of the majority of health centers in South Wollo Zone was within the “work to do” group. Therefore, the local government and other concerned bodies should monitor and support health centers to increase their preparedness and to build their capacity.Keywords: COVID-19, preparedness, health centers, South Wollo Zone, Ethiopia